Aristotle’s principles as conditions - Llovet Abascal, Jose Maria (Griot : Revista de Filosofia, 2021)
In this paper I will argue that when Aristotle uses the word ‘ἀρχή’ (commonly translated as ‘principle,’ ‘beginning,’ ‘origin,’ or ‘starting-point’) he is often referring to what we call a condition, whether necessary, sufficient or necessary and sufficient. To this end I will discuss how conditions for being, change, and knowledge, as identified by Aristotle, can be equated to ontological, physical and noetic principles, respectively.